Bioprosthetic valve oversizing is associated with increased risk of valve thrombosis following TAVR. Issue 3 (6th July 2020) - Simpson, Timothy F.; Tuohy, Craig V.; Rajotte, Katherine; Golwala, Harsh; Fuss, Cristina; Song, Howard K.; Zahr, Firas; Chadderdon, Scott M.
Abstract: Background: Hypoattenuating leaflet thickening (HALT), the radiographic manifestation of transcatheter heart valve thrombosis, is commonly identified following transcatheter aortic valve replacement (TAVR) and associated with increased risk of stroke and structural valve deterioration. While anticoagulation effectively resolves HALT, routine use remains controversial. We aimed to identify hemodynamic, anatomic, and comorbid predictors of HALT. Methods: We evaluated consecutive patients with severe aortic stenosis who underwent TAVR with Edwards SAPIEN 3 bioprosthesis at a single center between June 1, 2018 and October 30, 2019. Patients on anticoagulation and those receiving valve‐in‐valve were excluded. Clinically driven computed tomography (CT) imaging was performed to assess for HALT at the discretion of the treating valve team. Results: A total of 78 patients with a mean age of 78 ± 10 years and STS risk score 5.5 ± 3.3% were analyzed. HALT was identified in 11 (14.1%) patients. Compared to controls, those with HALT had smaller annular areas, 435 ± 57 mm 2 vs. 489 ± 79 mm 2 ( p = .032), but received comparable size valves. In multivariate regression, valve oversizing by more than 20% was associated with increased risk of HALT, OR 23.5, 95% CI 2.5–223, ( p = .006). After initiation of anticoagulation, patients with HALT had similar rates of stroke, major bleeding, and all‐cause mortality out to an average of 243 days. Conclusions: In this pragmatic study of patients undergoing TAVR with SAPIEN 3 valves, we report the novel finding that oversizing by more than 20% was independently associated with increased risk of HALT. These findings warrant confirmation in larger and prospective trials.